2021
DOI: 10.1002/ejic.202100415
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Photoswitching in a Series of Metal‐Organic Frameworks Loaded with Different Anthracenes

Abstract: The confinement of luminescent guest molecules in porous host materials can induce photophysical properties different from either component in isolation. In this work, we studied several host‐guest systems consisting of anthracene and its substituted analogs adsorbed in a series of metal‐organic frameworks (MOFs) and inorganic molecular sieves. Fluorescence photoswitching of the guest molecules through photoinduced dimerization is observed only in MOFs with a favorable pore volume and geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Continuing its work, Ameloot et al also encapsulated ANT in MFM-300(Sc). 144 The loading resulted in 1.8 ANT per pore and a broad fluorescence signal was exhibited at 500 nm, indicating the excimer formation within MFM-300(Sc). However, no photo-change of emission from excimer to monomer was observed after UV irradiation due to the reduced pore size of MFM-300(Sc) compared to ZIF-8.…”
Section: Host–guest Chemistrymentioning
confidence: 99%
“…Continuing its work, Ameloot et al also encapsulated ANT in MFM-300(Sc). 144 The loading resulted in 1.8 ANT per pore and a broad fluorescence signal was exhibited at 500 nm, indicating the excimer formation within MFM-300(Sc). However, no photo-change of emission from excimer to monomer was observed after UV irradiation due to the reduced pore size of MFM-300(Sc) compared to ZIF-8.…”
Section: Host–guest Chemistrymentioning
confidence: 99%
“…Particularly, a small change in the polarity and shape of MOF nanochannels can result in a large shift in emission despite similar pore sizes. From a survey of the field, it is observed that excimers formation of various dyes, such as naphthalene, , anthracene (Ant), pyrene, , and linkers, , within MOFs leads to progression in a number of fields, including modulation of emitting color and thermosensitive luminescence. Based on these findings, MOFs-confined dyes should be a good platform to explore the relationship between components and properties.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), which are composed of inorganic nodes and organic linkers, have received much attention over recent decades. MOFs offer a wide range of applications, such as gas storage and separation, catalysis, and sensing. The characteristic features of MOFs lie in their highly regular nanospaces that vary in accordance with their components. It is these advantages that enable us to achieve the precise assembly control of a variety of guest species, ranging from gas molecules to polymers, within the nanochannelsthus offering the potential to obtain host–guest synergies and new functions that are superior to those of the individual components. , …”
Section: Introductionmentioning
confidence: 99%